Studi Kasus: Asuhan Keperawatan pada Orang Dewasa dengan Isolasi Sosial: Case Study: Nursing Care for Adults with Social Isolation - Irma Herliana; Yeni Koto (Journal of Nursing Education and Practice, 2021)
Introduction: Mental disorders are individual behavior patterns associated with a symptom of suffering and weakness in one or more important functions of the human being, namely psychological, behavioral, biological functions, these disorders affect the relationship between themselves and society. Objectives: The purpose of this study was to determine the appropriate nursing care and intervention in patients with social isolation. Method: The design in this study is a case study design using a nursing process approach. The sample in this study was Mrs. B. The sampling technique used was simple random sampling. The research was conducted at X Hospital in April 2021. Data was collected by means of interviews, observations, and documentation studies. The research instrument is the researcher himself with the assessment guide tool. The nursing process approach carried out by researchers includes the following stages: Assessment Researchers collect data, both from respondents/patients. Nursing diagnoses, make nursing interventions, implement and then carry out nursing evaluations. Result: Implementation strategy 1 (SP1): helping the client identify the causes of the client's social isolation, discussing with the client the advantages of interacting and the disadvantages of not interacting with others, teaching the client how to get to know one person and encouraging the client to include practice talking to people others into daily activities. Implementation Strategy 2 (SP2): evaluates the client's daily schedule of activities, provides opportunities for clients to practice how to get to know one person, and helps clients include talking to other people as one of their daily activities. Implementation Strategy 3 (SP3): evaluate the client's daily activity schedule, provide opportunities for the client to get acquainted with two or more people, and encourage the client to include it in the daily activity schedule. Conclution: Nursing care for Mrs. B found that the first priority nursing problem is social isolation.